Diet dependent metabolic responses in three generalist insect herbivores Spodoptera spp. (April 2016) - Roy, A.; Walker, W.B.; Vogel, H.; Chattington, S.; Larsson, M.C.; Anderson, P.; Heckel, D.G.; Schlyter, F.
Abstract: Adaption to dietary changes is critical in the evolution of host plant ranges in polyphagous insects. We compared three taxa of lepidopteran herbivores from the predominantly generalist genus Spodoptera showing different degrees of polyphagy: Spodoptera littoralis, with a broad host range including both mono- and dicotyledonous plants, and two Spodoptera frugiperda strains [Corn (i.e. maize) (C) and Rice (R)] adapted primarily to different grass species. When feeding on maize we show a lower performance in the broad generalist taxon compared to the grass adapted taxa. Among these taxa, the maize adapted S. frugiperda C-strain generally performed better than the R-strain on maize leaves. On artificial pinto diet, all taxa performed well. Our RNA-Seq analysis of midgut transcriptomes from 3rd instar larvae feeding on maize showed broader transcriptional readjustments in the generalist S. littoralis compared to grass adapted S. frugiperda strains. Substantial alteration in the expression levels of midgut physiological function related transcripts, such as digestive and detoxifying enzymes, transporters, immunity, and peritrophic membrane associated transcripts, existed in all taxa. We found high background expression of UDP-glucosyl transferases, which are known to neutralize maize leaf toxins, in the maize adapted S. frugiperda C-strain, contributing to its fitness on maize compared to the R-strain. Our findings provide evidence for divergent diet specific response of digestive physiology within these Spodoptera taxa. Unexpectedly, the C- and R-strains of S. frugiperda fed on the same diet showed large differences in expression patterns between these two closely related taxa. Graphical abstract: Highlights: The reaction-norms of RNA-Seq and feeding performance data corresponds within taxa. We found highest overall upregulation in generalist S. littoralis on maize. Larval feeding on maize gives differential expression of key function midgut genes. Strain-differences in UGT enzymes contribute to fitness differences on maize. Alimentary divergence of the Corn/Rice strains was surprisingly high.